Antihyperglycemic effect and phytochemical investigation of Rubia cordifolia (Indian Madder) leaves extract - Khan Muhammad Shafiq (De Gruyter, 2021)
Medicinal plants are used as an important source of medicines in pharmaceutical industry. Rubia cordifolia is widely used to cure diabetes mellitus. Present study was aimed to investigate the antihyperglycemic effects of different fractions of R. cordifolia leaves and to analyze its antioxidant effect and phytochemical composition. Male albino mice were randomly distributed into seven groups (n = 7). Group-I was normal control, group-II was Alloxan (100 mg/kg)-induced diabetic control, and group-III was standard drug (Glibenclamide 0.5 mg/kg)-treated group. Animals in groups IV–VII were treated with n-hexane fraction, ethyl acetate fraction, n-butanol fraction and aqueous fraction of R. cordifolia, orally administered (100 mg/kg) once daily up to 28 days after Alloxan induction, respectively. Methanolic extract (ME) and fractions of R. cordifilia were analyzed for antioxidant activity and quantification of total phenolic content and total flavonoid content. HPLC of ME and most active fractions were performed. The results showed that RCEF (G-V) and RCBF (G-VI) have significantly (P < 0.05) reduced the increased level of glucose as compared to toxicant control group. It was further revealed that EF and BF have higher antioxidant activity (having IC50 34.9, 36.86 (µg/mL)) owing to phenolic and flavonoid identified by HPLC.